SOCIAL PANIC DISORDER AND ITS IMPACTS - Barroso, Marianna Leite; Maranhão, Thércia Lucena Grangeiro; Batista, Hermes Melo Teixeira; Neves, Fernanda Pereira de Brito; Oliveira, Gislene Farias de (Amadeus International Multidisciplinary Journal, 2018)
Panic disorder has been increasingly focused on health services and the media, where it affects young people aged 20-40. The incidence of these disorders affects 22% of the adult world population. Of these, 2.8% are grouped in severe disorders (schizophrenia, manic-depressive psychosis and severe forms of depression, panic syndrome and obsessive-compulsive disorder) in adults (Stuart, Laraia, 2002). This study aims to identify the risk factors for the development of Panic Disorder (PD), through the literature consulted; analyze the authors’ discourse and provide health professionals with the necessary subsidies for prevention and early intervention in the presence of possible signs and symptoms of PD. This is a bibliographic study carried out in libraries, the internet, scientific technical books and monographs. The results evidenced that in Brazil there is still no research that shows the real incidence of people affected with this syndrome. It is hoped that this discourse can guide the work of health professionals - specifically nurses - in the development of the syndrome and provide the means for adequate care directed at the patients and their families. Keywords: Panic Disorder; Risk factors; Intervention; Prevention.